Construction of New Standardized Attribute Control Chart based on defects per million opportunities - Dashty Ismil Jamil; Dlshad Mahmood Saleh; Alan Ghafur Rahim (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
To understand the concepts of Six Sigma, the concepts of Defects Per Unit (DPU) and Defects Per Opportunities (DPO) need to be introduced. DPU and DPO have different implications from attribute and variable data perspectives. The aim of this paper is to Construction quality control chart, which is Standardized attribute control chart based on defects per million opportunities (dpmo) to justify the efficiency and sensitively of the new chart for detecting are out of control cases. Using example, it was found that the examined processes were in control on both charts .The chart suggested herein may be useful for companies practicing Six Sigma process. These charts can be used to replace existing Shewhart control charts implemented when companies first started implementing Six Sigma.